Mdluli Backstories and Biographies: Shaka Zulu and the Persistence of amalala Identities (Historia, 2024)
The multiple accounts of Nomsimekwana Mdluli of Mkhambathini from the nineteenth and twentieth centuries provide an opportunity to examine how a small polity in central Natal confronted the position of King Shaka Zulu in accounts of their past. Nomsimekwana kaMcoseli experienced the centralisation of polities east of the Drakensberg Mountains in the late eighteenth and early nineteenth centuries that disturbed life at Mkhambathini, near the confluence of the Msunduze and Mngeni rivers. Forced to pledge their allegiance to other polities or come under attack, Mcoseli, his heir Nomsimekwana, and their followers affiliated themselves first with the Ngwane, later the Mkhize, then the Zulu, and eventually the British. Their associations waned and shifted as the threats changed – armies, hunger, marauders cast as amazimu, and Boer settlers – before Nomsimekwana Mdluli finally returned home to re-establish a chiefdom from the remnants who survived the transformation of the region. I flesh out the biographies and backstories of those involved in the creation and afterlives of these oral accounts of the Mdluli past. These accounts stress marginality and the impact of state consolidation on an amalala polity of Natal, as well as the persistence of amalala identities into the mid-twentieth century.
Keywords: oral accounts; traditional authority; Shaka Zulu; Zulu Kingdom; Zulu Society; KwaZulu-Natal; amalala